2017
DOI: 10.1038/cddis.2016.199
|View full text |Cite
|
Sign up to set email alerts
|

Star-PAP, a poly(A) polymerase, functions as a tumor suppressor in an orthotopic human breast cancer model

Abstract: Star-PAP is a noncanonical poly(A) polymerase and required for the expression of a select set of mRNAs. However, the pathological role of Star-PAP in cancer largely remains unknown. In this study, we observed decreased expression of Star-PAP in breast cancer cell lines and tissues. Ectopic Star-PAP expression inhibited proliferation as well as colony-forming ability of breast cancer cells. In breast cancer patients, high levels of Star-PAP correlated with an improved prognosis. Moreover, by regulating the expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 41 publications
1
16
0
Order By: Relevance
“…The iSCRIPT cDNA synthesis kit was used to synthesise 300ng of cDNA whereas KAPA Taq PCR was used for reverse transcription PCR (RT-PCR). The real time PCR was achieved by KAPA SYBR FAST qPCR Master Mix (2X) kit from Kapa Biosystems according to the manufacturers' guidelines and the primer sequences for performing both RT-PCR and Real-Time PCR are provided in S3 Table [51][52][53][54][55][56][57][58][59][60][61][62][63][64][65][66][67][70][71][72][73][74][75][76]. For each gene, the average C(t) value was determined and was normalised to housekeeping (GAPDH) mRNA levels.…”
Section: Reverse-transcription-pcr and Real-time Pcrmentioning
confidence: 99%
“…The iSCRIPT cDNA synthesis kit was used to synthesise 300ng of cDNA whereas KAPA Taq PCR was used for reverse transcription PCR (RT-PCR). The real time PCR was achieved by KAPA SYBR FAST qPCR Master Mix (2X) kit from Kapa Biosystems according to the manufacturers' guidelines and the primer sequences for performing both RT-PCR and Real-Time PCR are provided in S3 Table [51][52][53][54][55][56][57][58][59][60][61][62][63][64][65][66][67][70][71][72][73][74][75][76]. For each gene, the average C(t) value was determined and was normalised to housekeeping (GAPDH) mRNA levels.…”
Section: Reverse-transcription-pcr and Real-time Pcrmentioning
confidence: 99%
“…Tails, and the enzymes that add them, are critical in a wide spectrum of biological events. For example, uridylation is implicated in tumorigenesis, proliferation, stem cell maintenance, and the immune response 1-10 and regulated poly(A) addition in early development, cancer, and memory [11][12][13][14][15][16][17] . Unbiased and global approaches with single-nucleotide resolution are needed to uncover new types of tails and alternate modification systems that may have gone unnoticed.…”
Section: Introductionmentioning
confidence: 99%
“…We have established Star-PAP as a negative regulator of cellular invasiveness in breast cancer cells, indicating a putative role of Star-PAP in preventing cancer metastasis. A recent study has shown a role of Star-PAP as a tumor suppressor that prevents cell proliferation by a yet undefined mechanism ( 46 ). Star-PAP antitumor activity was implicated through a previously identified Star-PAP target, the apoptotic BIK gene ( 19 ).…”
Section: Discussionmentioning
confidence: 99%